2012
DOI: 10.1182/blood-2011-07-367680
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow transplantation for correcting hemophilia A in mice

Abstract: To better understand cellular basis of hemophilia, cell types capable of producing FVIII need to be identified. We determined whether bone marrow (BM)-derived cells would produce cells capable of synthesizing and releasing FVIII by transplanting healthy mouse BM into hemophilia A mice. To track donor-derived cells, we used genetic reporters. Use of multiple coagulation assays demonstrated whether FVIII produced by discrete cell populations would correct hemophilia A. We found that animals receiving healthy BM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 47 publications
3
65
2
3
Order By: Relevance
“…We also found that HA mice can be treated by reconstitution of healthy BM, indicating that BM−derived hematopoietic or mesenchymal cells can produce and secrete FVIII. 23 This study built on these possibilities by investigating whether human LSEC, hepatocytes or peripheral blood, cord blood and BM cells may be suitable for cell therapy in HA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that HA mice can be treated by reconstitution of healthy BM, indicating that BM−derived hematopoietic or mesenchymal cells can produce and secrete FVIII. 23 This study built on these possibilities by investigating whether human LSEC, hepatocytes or peripheral blood, cord blood and BM cells may be suitable for cell therapy in HA.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed previous findings of FVIII expression in myeloid cells in the mouse. 23 We, therefore, explored, in both humans and mice, which hematopoietic cell populations express FVIII (Figure 2 and Online Supplementary Figure S2). Peripheral blood monocytes and monocyte-derived macrophages expressed FVIII at the mRNA and protein levels.…”
Section: Factor VIII Expression In Bone Marrow and Peripheral Blood Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These include acute myeloid leukemia and acute lymphoblastic leukemias caused by translocations of the Mixed Lineage Leukemia (MLL) gene, [2][3][4] fusions of the HOXA9 gene that produce a novel HOXA9-NUP98 fusion protein in acute myeloid leukemia, 5 and T-cell acute lymphoblastic leukemias that have translocations between the TCRβ and HOXA9/A10 loci. 6 Interestingly however, despite this seemingly central role in a subset of acute leukemias, Hoxa9 expression alone is only weakly oncogenic in mouse leukemia models and usually requires a second "hit" via overexpression of Meis1, 7,8 or in some cases Pbx3. 9 Much work has been done trying to understand the molecular function of the HOXA9 protein.…”
Section: What Are the Implications Of These Findings For Cellular Andmentioning
confidence: 99%
“…8 Notably, in a series of experiments in hemophilia A mice, injection of isolated CD11 + human monocytes resulted in a transient increase in the circulating levels of factor VIII; the protein was biologically active, as demonstrated by the improved survival of animals upon hemostatic challenge to the macrocirculation (tail clip assay). Furthermore, hemophilia A mice that received cord bloodderived CD34 + cells from wild-type donors following total body irradiation experienced a dose-dependent elevation of factor VIII levels and improvement of the bleeding phenotype upon vascular injury.…”
mentioning
confidence: 99%